Type Synthesis of Fully-decoupled Three-rotational and Three-translational Parallel Mechanism - Zhou Hui; Cao Yi (Jixie chuandong)
Through the analysis of the input and output characteristic of the full-coupled parallel mechanism,based on the theory of screws and the principle of individual driving,a method of structural synthesis of fully-decoupled three-translational and three-rotational（ 3R3T） parallel mechanism is proposed. Firstly,based on the requirement of the Jacobian matrix of full-coupled parallel mechanism is the nonzero diagonal matrix,by using the screw theory,both the positive and the inverse Jacobian matrix meeting the expected requirement are constructed. The actuation screws of branch chain drive pair acting on the moving platform is determined,and the motion screw system of corresponding branched chain is obtained,and the branch chain structure screw system configuration can be completed by this. Finally,according to the full-coupled parallel mechanism branch combination principle,the six branched chains is selected to link motion platform,a lot of fully-decoupled 3R3T parallel mechanisms are obtained. The output motion of the synthesized fully-decoupled parallel mechanism is provided by independent input of branched chain,and the positive and the inverse Jacobian matrix is always stay for diagonal matrix in the moving process,it is belong to fully-decoupled parallel mechanism. The structure of such mechanism is compacted,control is simple,and it also has good prospect.